The enigma of 1989 : the USSR and the liberation of Eastern Europe - Lévesque, Jacques (Univ. of California Press, 1997)
Based on interviews and research "in Russia, Czechoslovakia, Hungary, Poland, and the other ex-Warsaw Pact countries, this book traces the nuances of each country's case as a set of continually changing, mutually reinforcing causes and effects."--Jacket.